Comparative genomics analysis in Prunoideae to identify biologically relevant polymorphisms. Issue 7 (13th June 2013) - Koepke, Tyson; Schaeffer, Scott; Harper, Artemus; Dicenta, Federico; Edwards, Mark; Henry, Robert J.; Møller, Birger L.; Meisel, Lee; Oraguzie, Nnadozie; Silva, Herman; Sánchez‐Pérez, Raquel; Dhingra, Amit
Summary Prunus is an economically important genus with a wide range of physiological and biological variability. Using the peach genome as a reference, sequencing reads from four almond accessions and one sweet cherry cultivar were used for comparative analysis of these three Prunus species. Reference mapping enabled the identification of many biological relevant polymorphisms within the individuals. Examining the depth of the polymorphisms and the overall scaffold coverage, we identified many potentially interesting regions including hundreds of small scaffolds with no coverage from any individual. Non‐sense mutations account for about 70 000 of the 13 million identified single nucleotide polymorphisms (SNPs). Blast2GO analyses on these non‐sense SNPs revealed several interesting results. First, non‐sense SNPs were not evenly distributed across all gene ontology terms. Specifically, in comparison with peach, sweet cherry is found to have non‐sense SNPs in two 1‐aminocyclopropane‐1‐carboxylate synthase (ACS) genes and two 1‐aminocyclopropane‐1‐carboxylate oxidase (ACO) genes. These polymorphisms may be at the root of the nonclimacteric ripening of sweet cherry. A set of candidate genes associated with bitterness in almond were identified by comparing sweet and bitter almond sequences. To the best of our knowledge, this is the first report in plants of non‐sense SNP abundance in a genus being linked to specific GO terms.